The position of the Republic of Kazakhstan in resolving the conflict in Ukraine (International relations and international law Journal, 2016)
The article deals with the problem of the conflict in Ukraine, and the role of the Republic of Kazakhstan in this crisis. Particular importance is attached to initiatives and proposals of Nursultan Nazarbayev to resolve the conflict, comprehensively describes the chronicle of events. Ukrainian crisis is the most serious and urgent conflict in modern international processes. Differences between Europe and Russia, imposing sanctions, the proliferation of new conflicts – all of this is a consequence of the conflict in Ukraine, which began in February 2014. The study describes in detail the events on the Maidan, and draws a parallel with the 2004 Orange Revolution. The fully set forth the position of the Republic of Kazakhstan in this problem. On the basis of the study authors have systematically analyzed the current situation and further prognosis made for the deployment of the events in Ukraine.
Keywords: Republic of Kazakhstan; Ukraine; the Russian Federation; foreign policy; Ukrainian conflict